Financial Performance And Stock Valuation: An Analysis Of PT FKS Food Sejahtera Tbk Post-Acquisiton - Tanti Kurnia Sutanto; Taufik Faturohman (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2026)
This study explores the financial performance and market valuation of PT FKS Food Sejahtera Tbk (FFS, IDX: AISA), formerly PT Tiga Pilar Sejahtera Food Tbk, following its acquisition by FKS Group. The research is motivated by the gap between the company’s improving fundamental performance and declining market price, which raises questions about valuation efficiency, information asymmetry, and optimal capital allocation. The study uses a qualitative methodology consisting of Discounted Cash Flow (DCF) model based on Free Cash Flow to the Firm (FCFF), relative valuation using Price to Earnings and Price to Book multiples benchmarked against average food manufacturing peers, and sensitivity analysis across WACC and plausible terminal growth assumptions. The fundamental analysis indicates consistent operational improvement period 2021–2025, along with consistent revenue growth. Despite these improvements, DCF and relative valuation confirm significant market gap. The DCF model yields an intrinsic value of IDR 234 per share against a prevailing market price of IDR 134 representing a discount of approximately 43% to intrinsic value with a margin of safety validated across all sensitivity scenarios. To address this gap, the study develops three share buyback scenarios using a fixed-price tender offer mechanism. The study concludes that FFS exhibits the characteristics of a value recovery situation requiring both a credible shareholder return mechanism and sustained investor relations initiatives to reduce the persistent market discount